MOOCs: A Comparative analysis between Indian scenario and Global scenario - Gomathi Sankar Jaganathan, Dr.; N. Sugundan, Dr.; Siranjeevi Sivakumar, Mr. (International Journal of Engineering and Technology, 2018)
Massive open online courses (MOOCs) are most recent and prominent trends in higher education. MOOCs has witnessed tremendous growth with huge enrolment. Having recorded large enrolment, India has initiated various projects such as NPTEL, IITBX, and SWAYAM. Many online platforms have been developed to provide online courses to encourage continuing education. This study detailed the characteristics of MOOCs along with various online platforms across the world. The authors compare the growth of Indian MOOCs with global scenario and list of providers who develop and deliver online courses and possible challenges of MOOCs implementation in India.Â Â Â